Fuel price elasticities in the U.S. combination trucking sector. (July 2015) - Winebrake, James J.; Green, Erin H.; Comer, Bryan; Li, Chi; Froman, Sarah; Shelby, Michael
Highlights: We estimate fuel price elasticities for combination trucks in the US between 1970 and 2012. We apply an econometric approach using national transportation datasets. Fuel price elasticities have shifted from elastic to inelastic over time. The results have implications for understanding trucking responses to fuel price changes. Abstract: This paper estimates fuel price elasticities of combination trucking operations in the United States between 1970 and 2012. We evaluate trucking operations in terms of vehicle miles traveled and fuel consumption for combination trucks. Our explanatory variables include measures of economic activity, energy prices, and indicator variables that account for important regulatory shifts and changes in data collection and reporting in national transportation datasets. Our results suggest that fuel price elasticities in the United States' trucking sector have shifted from an elastic environment in the 1970s to a relatively inelastic environment today. We discuss the importance of these results for policymakers in light of new policies that aim to limit energy consumption and reduce greenhouse gas emissions from heavy-duty vehicles.